Teacher Performance Management in Improving Islamic Religious Education (IRE) Lesson Learning - Een Nurjannah; Engkus Kuswarno; Ahmad Mudrikah; Usep Kosasih (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2021)
The management of teacher performance coaching is very important as a hard effort to improve teacher performance, especially in the learning process. PAI teacher performance coaching which is carried out in a planned and structured manner by implementing management functions will improve the quality or quality of PAI teacher learning itself and in the end, will improve student achievement as learning citizens. Teacher performance coaching carried out at SMPN 13 and SMPN 22 Bandung, has generally been well implemented with reference to the vision and mission, as well as the goals that must be realized. Based on the results of research findings on all aspects of management functions from planning, organizing, implementing and controlling as well as security factors and efforts to overcome the problem of increasing learning through management of teacher performance coaching have been implemented in the daily work activities of teachers in schools, especially in Islamic Studies subjects optimal. Thus, it is very important to discuss the findings of this study. Some things that become notes in the future for improving the management of Islamic education teacher performance coaching by PAIS supervisors and school principals are focused on fostering work ethics, building morals, and teacher character. This is very important to do as an effort to create teachers who are not only smart and creative but also have great character and have great character.